Visualizing the Geography of the Diseases of China: Western Disease Maps from Analytical Tools to Tools of Empire, Sovereignty, and Public Health Propaganda, 1878–1929. Issue 3 (11th October 2017) - Hanson, Marta
Argument: This article analyzes for the first time the earliest western maps of diseases in China spanning fifty years from the late 1870s to the end of the 1920s. The 24 featured disease maps present a visual history of the major transformations in modern medicine from medical geography to laboratory medicine wrought on Chinese soil. These medical transformations occurred within new political formations from the Qing dynasty (1644–1911) to colonialism in East Asia (Hong Kong, Taiwan, Manchuria, Korea) and hypercolonialism within China (Tianjin, Shanghai, Amoy) as well as the new Republican Chinese nation state (1912–49). As a subgenre of persuasive graphics, physicians marshaled disease maps for various rhetorical functions within these different political contexts. Disease maps in China changed from being mostly analytical tools to functioning as tools of empire, national sovereignty, and public health propaganda legitimating new medical concepts, public health interventions, and political structures governing over human and non-human populations.